Using Self-Management and Visual Cues to Improve Responses to Nonverbal Social Cues in Adults With Autism Spectrum Disorder. Issue 3 (May 2022) - Cohen, Shereen; Koegel, Robert; Koegel, Lynn Kern; Engstrom, Erin; Young, Kurtis; Quach, Anthony
Many individuals with Autism Spectrum Disorder (ASD) experience challenges with social communication, including recognizing and responding to non-verbal cues. The purpose of this study was to assess the efficacy of self-management combined with textual cues to teach adults with ASD to recognize and respond to nonverbal expressions of boredom and confusion during social conversation. A multiple baseline across participants design was used to assess the efficacy of this intervention for three participants. Results showed substantial gains across all participants in their recognition and responsiveness to the targeted nonverbal cues. Moreover, this skill maintained after the completion of intervention and generalized to novel conversation partners and settings with large effect sizes. The findings add to the literature base on interventions for adults with ASD, and further support the use of self-management and textual cues as effective intervention strategies for improving nonverbal communication.